1999
DOI: 10.1007/s004060050089
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase immunoreactivity in the locus coeruleus is reduced in depressed non-suicidal patients but normal in depressed suicide patients

Abstract: Noradrenergic neurons of the locus coeruleus (LC) have been implicated in the neurobiology of depression and suicidal behavior. The current postmortem study determined numbers of noradrenergic neurons by immunostaining the synthesizing enzyme tyrosine hydroxylase in the LC of 12 non-elderly depressed patients with a mood disorder as compared to 12 age- and sex-matched normal controls. Six patients were suicide victims, the other six patients died of natural causes. Non-suicidal patients had fewer neurons immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 42 publications
4
23
0
2
Order By: Relevance
“…The mRNA TH levels in the LC refl ect previous results showing no differences in TH immunoreactivity between depressed suicide victims and normal subjects (Baumann et al 1999). However, these results seem to confl ict with previous studies reporting increased TH activity in the LC of suicide victims (Ordway et al 1994;Ordway 1997), although in the latter paper only two suicide victims with a premorbid diagnosis of depression were included, while the diagnosis Increased mRNA expression of cytochrome oxidase in DRN of the other seven suicides in the study group was uncertain.…”
Section: O R I G I N a L R E S Esupporting
confidence: 71%
See 1 more Smart Citation
“…The mRNA TH levels in the LC refl ect previous results showing no differences in TH immunoreactivity between depressed suicide victims and normal subjects (Baumann et al 1999). However, these results seem to confl ict with previous studies reporting increased TH activity in the LC of suicide victims (Ordway et al 1994;Ordway 1997), although in the latter paper only two suicide victims with a premorbid diagnosis of depression were included, while the diagnosis Increased mRNA expression of cytochrome oxidase in DRN of the other seven suicides in the study group was uncertain.…”
Section: O R I G I N a L R E S Esupporting
confidence: 71%
“…However, these results seem to confl ict with previous studies reporting increased TH activity in the LC of suicide victims (Ordway et al 1994;Ordway 1997), although in the latter paper only two suicide victims with a premorbid diagnosis of depression were included, while the diagnosis Increased mRNA expression of cytochrome oxidase in DRN of the other seven suicides in the study group was uncertain. Taken together, these results suggest that there might be a dissociation between depression per se, which may be associated with reduced noradrenergic activity (Baumann et al 1999), and suicidal symptoms, which may be associated with increased activity (Ordway et al 1994), thus masking the effects on the post depression suicide victims.…”
Section: O R I G I N a L R E S Ementioning
confidence: 89%
“…Altamura et al (2010), Baumann et al (1999), Bellivier et al (2000), Benedetti et al (2011), Berrettini et al (1986), Campos et al (2010), D’Ambrosio et al (2012), De Luca et al (2005a, 2005b, 2006, 2009), Dowlatshahi et al (1999), Dracheva et al (2008), Evans et al (2012), Feldcamp et al (2008), Finseth et al (2014), Jimenez et al (2013), Kamali et al (2012), Kim et al (2002, 2007, 2008), Le-Niculescu et al (2013), Leszczynska-Rodziewicz et al (2014), Lopez et al (2007), Mahon et al (2012), Malloy-Diniz et al (2011), Matsuo et al (2010), Monfrim et al (2014), Nery et al (2014), Nery-Fernandes et al (2012), Neves et al (2008, 2010), Park et al (2013), Perlis et al (2012), Pinto et al (2011), Pompili et al (2008), Shabani et al (2013), Sher et al (2006, 2012), Singhal et al (2014), Souery et al (2001), Stange et al (2014), Suttajit et al (2013), Thibodeau et al (2013), Tidemalm et al (2014), Tochigi et al (2008), Tsai et al (1999a), Vuksan-Cusa et al (2009) and Willour et al (2012).…”
Section: Figurementioning
confidence: 99%
“…Recent neurobiological studies of the human brain have demonstrated that depression and suicide are, despite some shared features, two distinct phenomena. However, no unequivocal diagnostic criteria enabling their differentiation have been developed so far (Baumann et al 1999;Mann et al 2000;Arango et al 2002;Stockmeier 2003;Bielau et al 2005).…”
Section: Introductionmentioning
confidence: 99%